On properties of the modified clay-gypsum binder based on the clay-gypsumfrom the Khojakul deposit - Ishanovich, Adilkhodzhaev Anvar; Muminovich, Makhamataliev Irkin; Torekhanovich, Ilyasov Allanazar; Orynbaevich, Asamatdinov Marat; Kabylbekuly, Embergenov Kurbanbek (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of studies on the properties of a modified clay-gypsum binder based onthe clay-gypsum from the Khojakul deposit (Republic of Karakalpakstan). The studies have shown that the best results are reached when using the following additives to the composition of a modified clay-gypsum binder: a superplasticizer C-3 and a hardening retarder – citric acid.